Antimicrobial resistance at a turning point: microbial drivers, one health, and global futures - Elbehiry, Ayman; Marzouk, Eman; Abalkhail, Adil (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) is a major health threat of the 21st century, undermining the effectiveness of modern medical interventions and reversing decades of progress in infection control. Its drivers include microbial evolution, horizontal gene transfer, inappropriate use in human and veterinary medicine, agricultural practices, environmental reservoirs, and uneven regulation. This review integrates microbial, clinical, and environmental perspectives within a One Health framework. At the microbial level, resistance arises through mutation, gene transfer, and biofilm-associated tolerance, with soil, wastewater, and wildlife serving as conduits for spreading resistance elements. Advances in diagnostics—including matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), whole-genome sequencing (WGS), digital PCR, and CRISPR-based assays are transforming detection and surveillance, but deployment remains uneven, particularly in low- and middle-income countries. Antimicrobial stewardship now extends beyond hospitals, supported by decision support systems, artificial intelligence (AI), and community programs; however, gaps in surveillance capacity and policy implementation continue to limit impact. One Health linkages connect agricultural use, wastewater, and wildlife exposure with human risk, embedding clinical decisions within ecological and veterinary contexts. Persistent gaps include fragmented regulation, limited involvement of microbiologists in policy development, and weak incentives for antibiotic innovation. Priority directions include biomarker-guided prescribing, CRISPR-directed antimicrobials, microbiome-sparing therapeutics, and genomics-informed surveillance that integrates clinical and environmental data. Positioning the clinical microbiology laboratory as an operational hub can align rapid diagnostics, interpretive reporting, antimicrobial stewardship, and integrated surveillance (GLASS, EARS-Net, NARMS, and wastewater/wildlife monitoring) on a common platform. Clear reporting triggers and concise case vignettes can translate laboratory results into actionable bedside decisions and policy measures across diverse resource settings, with measurable benefits for patient outcomes and public health.